The Emergence of the Infomercial in New Zealand 1993–1997 - Johnson, Rosser (The Political Economy of Communication, 2013)
In December 1993 television viewers in New Zealand were presented with a novel form of television; the infomercial (a 30-minute advertisement designed to appear as if it were a program). While such broadcasting had been a regular feature of American television since the 1950s, and had become more prevalent after 1984, non-traditional forms of 'hyper-commercial' broadcasting were unusual in the local context. This article uses published primary sources (from the specialist and general press), a content analysis of television schedules and interviews with infomercial producers and regulators to trace the emergence of the infomercial in the early 1990s. Specifically, it outlines three key reasons why the emergent infomercial form quickly thrived to the point where it became a flourishing televisual form and revenue stream for advertisers and broadcasters alike. It concludes by demonstrating the susceptibility of broadcasting systems to novel methods of revenue raising, especially when the wider economy is contracting or in recession.